A Glance at Terrorist Organizations from the Perspective of Organizational Theories - Sefer Yılmaz (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The problem of conceptualizing terrorist organization is still a controversial issue, even though it has been taken place in the literature heavily. In this essay, terrorist organizations will be approached in the context of organizational theories. Terrorist organizations will be introduced as exceptional structures besides being consistent with most of the organizational theories, departing from them in terms of strategies they adapt and life expectancy they experience. According to some theories such as institutional theory, population ecology approach and system theories, although being claimed to be excluded from the system by other organizations for they do not resemble and even threaten the existence of others and although being wanted to be eliminated by the system, terrorist organizations can be able to survive more than these theories contend.